A137 THERAPEUTIC DRUG MONITORING WITH INFLIXIMAB TROUGH LEVELS LEAD TO INCREASED INTERVENTION. (1st March 2018) - Stern, N C; Fedorak, R; Wong, K; Halloran, B P; Dieleman, L A; Huang, V; Peerani, F; Kroeker, K I
Abstract: Background: Therapeutic drug monitoring (TDM) of infliximab (IFX) as indicated in patients with loss of response (LOR) (known as reactive strategy) is a widely accepted strategy in the management of patients with inflammatory bowel disease (IBD). Proactive drug monitoring of IFX trough levels has been proposed as a way to pre-empt LOR and hopefully preserve IFX as a therapeutic options. The impact of proactive TDM at week 14, following induction therapy is not well studied. Aims: To compare week 30 remission rates in IFX IBD patients with week 14 TDM to those without TDM, as well as determine the proportion of patients with week 14 TDM that were dose escalated. Methods: This retrospective chart review in which ulcerative colitis (UC) and Crohn's disease (CD) patients 17 years of age or older that were on IFX for at least 30 weeks. Charts were reviewed for objective and subjective assessments of clinical remission, concomitant immunosuppressants and dose changes. Parameters of ± 1 week were allowed for trough level inclusion and ± 1 month for all other markers. Categorical and quantitative data were presented as proportions through a Chi-squared test and the t-test, respectively. All significance is assessed at p < 0.05. Results: In total, 240 patients initiated on IFX between January 2015 - June 2017 were identified and 156 patients were included in the final analysis. Eighty-four patients were excluded due to: clinical LOR at week 14 ( n =1) and patients not on IFX at week 30 ( n = 83). Clinical remission with TDM was not greater than those without TDM (69.4% - 84.8%; p = 0.049). Furthermore, dose escalation in patients was more common in patients with TDM than without TDM (77.3% - 30.4%; p < 0.001). Conclusions: In conclusion, proactive TDM was associated with more frequent dose escalation. Funding Agencies: None